1992
DOI: 10.1128/aac.36.8.1750
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rabies virus transcription in rat cortical neurons with the dissociative anesthetic ketamine

Abstract: In a previous study (B. P. Lockhart, H. Tsiang, P. E. Ceccaldi, and S. Guillemer, Antiviral Chem. Chemother. 2:9-15, 1991), we demonstrated an antiviral effect of the general anesthetic ketamine for rabies virus in neuronal cultures and in rat brain. This report describes an attempt to determine at what level ketamine acts on the rabies virus cycle in rat cortical neuron cultures. Immunofluorescence and [35S]methionine labelling of infected neurons showed that ketamine (1 to 1.5 mM) inhibited viral nucleoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…The findings indicate that caution should be taken before subjecting future human rabies patients to therapy with ketamine on the basis of the previous experimental work (15,16,20). There have been at least four patients treated with ketamine after the survivor received ketamine in 2004, and all of these patients progressed to fatal outcomes (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicate that caution should be taken before subjecting future human rabies patients to therapy with ketamine on the basis of the previous experimental work (15,16,20). There have been at least four patients treated with ketamine after the survivor received ketamine in 2004, and all of these patients progressed to fatal outcomes (7).…”
mentioning
confidence: 99%
“…The events in rabies virus infection that lead to CNS disease and a fatal outcome are still not well understood (6). Studies with rat cortical neurons and with a rat model suggested the possibility that the noncompetitive Nmethyl-D-aspartate acid (NMDA) antagonists ketamine and MK-801 might be effective therapeutic agents for human rabies (15,16,20) and that ketamine inhibits viral RNA genome transcription (15). Consequently, a working group recommended that ketamine be considered for the therapy of human patients with rabies (12).…”
mentioning
confidence: 99%
“…Ketamine is an anesthetic agent that is considered a potential therapeutic agent in the management of human rabies on account of its inhibitory effect on RNA transcription and Nmethyl D-aspartate receptor antagonistic function that might limit viral spreading in tissue [140,149]. Its ability to rapidly cross the BBB is of potential advantage in reaching the rabies virus within the CNS.…”
Section: Immunizationmentioning
confidence: 99%
“…Por otra parte, la ketamina es un antagonista del receptor de N-metil-D-aspartato con actividad específica contra la rabia en los modelos animales (43). Por todo lo anterior, se diseñó este protocolo como una estrategia para tratar de proteger el cerebro de la lesión, mientras se le permitía al sistema inmune desarrollar una respuesta natural y acabar con el virus.…”
Section: Figuraunclassified